Cartilage-hair hypoplasia in Finland: epidemiological and genetic aspects of 107 patients. - Mäkitie, O (1992)
Cartilage-hair hypoplasia (CHH) is an autosomal recessive form of metaphyseal chondrodysplasia characterised by short limbed short stature, hypoplastic hair growth, and impaired cell mediated immunity and erythrocyte production. The syndrome is exceptionally prevalent among the Finns and among the Old Order Amish in the United States; sporadic cases have been reported from other countries. An epidemiological and genetic study of CHH in Finland showed 107 patients, 46 males and 61 females, in 85 families. Eighteen of them had died, seven before the age of 1 year. The living patients ranged in age from 1 to 51 years, median 21 years. The incidence was estimated to be 1:23,000 live births. Consanguinity was found in two families and interfamilial relationships in 20 families. Geographical distribution of the birth places of the patients and their great grandparents showed accumulation in a small area in western Finland and regional clusters were seen in other parts of the country as well. The result of the segregation analysis was in accordance with recessive inheritance with reduced penetrance.